Development of a simple assay protocol for high-throughput screening of mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, U; Panchanadikar, V; Sarkar, Dhiman (Journal of Biomolecular Screening, 2005)
Mycobacterium tuberculosis glutamine synthetase (GS) is an essential enzyme involved in the pathogenicity of the organism. The screening of a compound library using a robust high-throughput screening (HTS) assay is currently thought to be the most efficient way of getting lead molecules, which are potent inhibitors for this enzyme. The authors have purified the enzyme to a > 90% level from the recombinant Escherichia coli strain YMC21E, and it was used for partial characterization as well as standardization experiments. The results indicated that the K-m of the enzyme for L-glutamine and hydroxylamine were 60 mM and 8.3 mM, respectively. The K-m for ADP, arsenate, and Mn2+, were 2 mu M, 5 mu M, and 25 mu M, respectively. When the components were adjusted according to their K-m values, the activity remained constant for at least 3 h at both 25 degrees C and 37 degrees C. The Z' factor determined in microplate format indicated robustness of the assay. When the signal/noise ratios were determined for different assay volumes, it was observed that the 200-mu l volume was found to be optimum. The DMSO tolerance of the enzyme was checked up to 10%, with minimal inhibition. The IC50 value determined for L-methionine S-sulfoximine on the enzyme activity was 3 mM. Approximately 18,000 small molecules could be screened per day using this protocol by a Beckman Coulter HTS setup.
Keywords: Beckman Coulter; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis

Development of a simple high-throughput screening protocol based on biosynthetic activity of Mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, Upasana; Sarkar, Dhiman (Journal of Biomolecular Screening, 2006)
A high-throughput screening protocol has been developed for Mycobacterium tuberculosis glutamine synthetase by quantitative estimation of inorganic phosphate. The K., values determined at pH 6.8 are 22 mM for L-glutamic acid, 0.75 mM for NH4Cl, 3.25 mM for MgCl2, and 2.5 mM for adenosine triphosphate. The K-m value for glutamine is affected significantly by the increase in pH of assay buffer. At the saturating level of the substrate, the enzyme activity at pH 6.8 and 25 degrees C is found to be linear up to 3 h. The reduction of enzyme activity is negligible even in presence of 10% DMSO. The Z' factor and signal-to-noise ratio are found to be 0.75 and 6.18, respectively, when the enzyme is used at 62.5 mu g/ml concentration. The IC50 values obtained at pH 6.8 for both L-methionine S-sulfoximine and DL-phosphothriacin are 500 mu M and 30 pM, respectively, which is lowest compared to the values obtained at other pH levels. The Beckman Coulter high-throughput screening platform was found to take 5 h 9 min to complete the screening of 60 plates. For each assay plate, a replica plate is used to normalize the data. Screening of 1164 natural product fractions/extracts and synthetic molecules from an in-house library was able to identify 12 samples as confirmed hits. Altogether, the validation data from screening of a small set of an in-house library coupled with Z' and signal-to-noise values indicate that the protocol is robust for high-throughput screening of a diverse chemical library.
Keywords: Beckman Coulter; biosynthetic activity; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis

Potential use of nitrate reductase as a biomarker for the identification of active and dormant inhibitors of mycobacterium tuberculosis in a THP1 infection model - Sarkar, Sampa; Sarkar, Dhiman (Journal of Biomolecular Screening, 2012)
The development of a macrophage-based, antitubercular high-throughput screening system could expedite discovery programs for identifying novel inhibitors. In this study, the kinetics of nitrate reduction (NR) by Mycobacterium tuberculosis during growth in Thp1 macrophages was found to be almost parallel to viable bacilli count. NR in the culture medium containing 50 mM of nitrate was found to be optimum on the fifth day after infection with M. tuberculosis. The signal-to-noise (S/N) ratio and Z-factor obtained from this macrophage-based assay were 5.4 and 0.965, respectively, which confirms the robustness of the assay protocol. The protocol was further validated by using standard antitubercular inhibitors such as rifampicin, isoniazid, streptomycin, ethambutol, and pyrazinamide, added at their IC90 value, on the day of infection. These inhibitors were not able to kill the bacilli when added to the culture on the fifth day after infection. Interestingly, pentachlorophenol and rifampicin killed the bacilli immediately after addition on the fifth day of infection. Altogether, this assay protocol using M. tuberculosis-infected Thp-1 macrophages provides a novel, cost-efficient, robust, and easy-to-perform screening platform for the identification of both active and hypoxic stage-specific inhibitors against tuberculosis.
Keywords: high-throughput screening; inhibitor; Mycobacterium tuberculosis; nitrate reductase; THP1